2014
DOI: 10.3892/ol.2014.2665
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic neuroectodermal tumor of infancy: A case report and review of the surgical treatment

Abstract: Melanotic neuroectodermal tumor of infancy (MNTI) is a rare, fast-growing, benign tumor originating from the neural crest. The tumor most often occurs during the first year of life. The predilection site of MNTI is the anterior maxilla, whereas lesions of the mandible are uncommon and account for only 6% of all cases. At present, the most common treatment for MNTI is surgical resection, however, tumor recurrence arises in 10–60% of cases. The optimal extent of surgical resection is a matter of debate; rapid gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 18 publications
5
18
0
3
Order By: Relevance
“…We also observed that lesions was seen as a rapidly growing asymptomatic bluish swelling, which corroborates the information previously published in the literature. 11,14,21 We observed that radical surgery is the best treatment approach, consistent with other previous studies. 13,18 Histologically, the tumor consists of a biphasic population of small neuroblast-like cells and larger melaninproducing epithelioid cells arranged in an alveolar architecture, with cords and trabeculae intersected by dense fibroblastic stroma.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We also observed that lesions was seen as a rapidly growing asymptomatic bluish swelling, which corroborates the information previously published in the literature. 11,14,21 We observed that radical surgery is the best treatment approach, consistent with other previous studies. 13,18 Histologically, the tumor consists of a biphasic population of small neuroblast-like cells and larger melaninproducing epithelioid cells arranged in an alveolar architecture, with cords and trabeculae intersected by dense fibroblastic stroma.…”
Section: Discussionsupporting
confidence: 90%
“…The tumor cells are typically negative for chromogranin, neurofilaments, S100 protein, and desmin. 11,14,21 We observed that radical surgery is the best treatment approach, consistent with other previous studies. 3,11,16,22 In our analysis, five cases reported regional lymph node metastasis and two were confirmed to be affected by the lesion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…El tumor neuroectodérmico melanótico de la Infancia (TNMI), es benigno infrecuente, originado en la cresta neural y compuesto por células productoras de pigmentos (melanina). 1 Fue descrito por primera vez en 1918 por Krompecher quien le dio el nombre de melanocarcinoma congénito; otros sinónimos incluyen: tumor neuroectodérmico pigmentado de la infancia, progonoma melanótico y odontoma epitelial melanótico. En 1966, Gorlin y Borello registraron niveles altos de ácido vanilmandélico (AVM), un marcador de tumores neurogénicos en estos pacientes por lo que se lo clasificó dentro del grupo de tumores de origen neurogénico.…”
Section: Introductionunclassified
“…3 Se estima que cerca del 92.8% se presentan en la cabeza y el cuello, con mayor frecuencia en el maxilar superior (60-80%), en el cráneo a nivel de la fontanela anterior más comúnmente (10,8%), mandíbula (6%) y en el cerebro (4,3%). 1 En raras ocasiones surgen en meninges, seno transverso, retina, mediastino, huesos, útero y epidídimo. Se presenta con mayor frecuencia (95%) durante el primer año de vida, con una edad pico entre 2 y 6 meses de edad y se han reportado pocos casos en adultos.…”
Section: Introductionunclassified